1 - Ways of (De)constructing and Shaping a City: Urban Shifts and Materiality in Dialogue with Global China in Lusaka, Zambia - Gerald Chungu, Gerald Chungu; Dittgen, Romain (Africa Development, 2021)
Lusaka’s ongoing construction boom and shifting urban landscape are seen as closely linked to a significant level of Chinese involvement, especially with regard to the building process. Although Chinese features in the cityscape are pervasive and have increased in recent years, visual reflections of this can be misleading. They do not reveal the extent to which global China is playing a part in altering the built environment and trajectories in a city marked by rapid urban growth, spatial inequality and uneven development. With a focus on the main and simultaneous trends that characterise Lusaka’s evolving urban morphology: densification, land-use change and sprawl, we explore if and to what degree Chinese capital (whether public or private) and participation contribute to producing a different kind of urbanity (in terms of direction and product). By unpacking the construction process, we argue that initiatives with some level of Chinese involvement largely plug into pre- existing patterns, replicate tendencies of urban development and, as such, constitute an integral part of the city-making process. From this perspective, Chinese influence on urban development processes needs to be understood through a “logic of supplementarity” – present and absent, identifiable and imperceptible – but as constantly operating within the core.